2010
DOI: 10.1002/bit.22611
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic oxidation of arsenite linked to chemolithotrophic denitrification in continuous bioreactors

Abstract: In this study, the anoxic oxidation of arsenite (As(III)) linked to chemolithotrophic denitrification was shown to be feasible in continuous bioreactors. Biological oxidation of As(III) was stable over prolonged periods of operation ranging up to 3 years in continuous denitrifying bioreactors with granular biofilms. As(III) was removed with a high conversion efficiency (> 92%) to arsenate (As(V)) in periods with high volumetric loadings (e.g. 3.5 to 5.1 mmol As Lreactor−1 d−1). The maximum specific activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The IC50 of As(III) to methanogenic activity in sludge has been reported to be as low as 15 μM (Sierra-Alvarez et al, 2004). In this study, As(III) was found to be an inhibitory substrate of AOCRB as was demonstrated previously with As(III)-oxidizing, denitrifying bacteria (Sun et al, 2010a). …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The IC50 of As(III) to methanogenic activity in sludge has been reported to be as low as 15 μM (Sierra-Alvarez et al, 2004). In this study, As(III) was found to be an inhibitory substrate of AOCRB as was demonstrated previously with As(III)-oxidizing, denitrifying bacteria (Sun et al, 2010a). …”
Section: Resultssupporting
confidence: 80%
“…Thus, there is a potential to utilize ClO 3 − to promote the bioremediation of As-contaminated sites through the bio-oxidation of As(III) to As(V). In a previous study, the anoxic oxidation of As(III) linked to chemolithotrophic denitrification was shown to be stable in continuous bioreactors (Sun et al, 2010a). It is well known that (per)chlorate (ClO 4 − and ClO 3 − ) reducing bacteria have the ability to oxidize reduced inorganic compounds such as elemental sulfur (S o ), elemental iron (Fe 0 ), and H 2 (Ju et al, 2008) in batch assays and experimental bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…The inoculum was obtained from a 2-l bench-scale upward flow anaerobic sludge bed As(III)-oxidizing denitrifying bioreactor after 466 days of operation (Sun et al 2010). The bioreactor was fed with As(III) (3.5 mM) as electron donor, NO 3 − (6.5 mM) as electron acceptor, and NaHCO 3 (8.0 mM) as major carbon source with a hydraulic retention time (HRT) of 1.1 d. The total suspended solids (TSS) and volatile suspended solids (VSS) content of the sludge was 6.08±0.18% and 5.76±0.23%, respectively, on a wet weight basis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently evidence is growing that microbial oxidation of As(III) can also occur under anoxic conditions in the presence of nitrate (NO 3 − ) (Oremland et al 2002; Rhine et al 2006; Sun et al 2008) or selenate (Fisher and Hollibaugh 2008). In a previous study, the anoxic oxidation of arsenite (As(III)) linked to chemolithotrophic denitrification was shown to be stable and efficient over prolonged periods of operation ranging up to 3 years in up-flow continuous bioreactors (Sun et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…It makes sense that such an ancient oxidase function evolved before the atmosphere became oxidizing, allowing arsenite oxidation to couple to energy production. In present-day Mono Lake, California, several strains of bacteria have been shown to be arsenite oxidizers that use nitrate or selenate as electron acceptors, coupling arsenite to ATP production (Fisher & Hollibaugh 2008, Oremland et al 2002), and have been adapted for use in bioreactors (Sun et al 2010a). Anoxygenic photosynthesis has also been found to be coupled to arsenite oxidation in microbial mats of cyanobacteria and photosynthetic bacteria from Mono Lake (Kulp et al 2008).…”
Section: Arsenic Oxidation and Reduction: Pathways For Energy Metabolmentioning
confidence: 99%